Building communities: reducing energy use in tenanted commercial property - Axon, C; Bright, S; Dixon, T; Janda, K; Kolokotroni, M; Bright, S (Taylor and Francis Group, 2012)
Reducing energy use in tenanted commercial property requires a greater understanding of buildings as communities. Tenanted commercial properties represent: (1) the divergent communities that share specific buildings; and (2) the organizational communities represented by multi-site landlord and tenant companies. In any particular tenanted space the opportunity for environmental change is mediated (hindered or enabled) through the lease. This discussion draws on theoretical and practical understandings of (1) the socio-legal relationships of landlords, tenants and their advisors; (2) the real performance of engineering building services strategies to improve energy efficiency; (3) how organizational cultures affect the ability of the sector to engage with energy-efficiency strategies; and (4) the financial and economic basis of the relationship between owners and occupiers. The transformational complexity stems from: (1) the variety of commercial building stock; (2) the number of stakeholders (solicitors, investors, developers, agents, owners, tenants and facilities managers); (3) the fragmentation within the communities of practice; and (4) leasehold structures and language. An agenda is proposed for truly interdisciplinary research that brings together both the physical and the social sciences of energy use in buildings so that technological solutions are made effective by an understanding of the way that buildings are used and communities behave. © 2012 Taylor and Francis.